On lip-sync: Three audio-visual vignettes from the 1970s - Gopinath, Gabrielle (The soundtrack (Bristol), 2011)
Why make a video that focuses exclusively on a speaker’s lip-syncing mouth? In the early 1970s, multiple artists made short films and videos that answer this description. This article considers three such works and offers an explanation of their significance. The videos and film shorts in question were made between 1969 and 1974 by Steina Vasulka, Bruce Nauman, and the collaborative team of Richard Serra and Nancy Holt. Each of these works presents a close-up view of the artist’s mouth. In two cases, these mouths fill nearly the entirety of the screen for the work’s duration. The mouths in question speak or sing; in each case, the audio track of the resultant sounds is imperfectly synced to the visible movements of the speaker’s mouth. As a result, lip-sync becomes not just an element of these works but their primary locus of interest. This article examines how each of these artists uses the recorded voice and the represented body to grapple with questions about the nature and meaning of existence in a mediated world. The alienation of sound from image that lip-sync failure makes visible is a metonym for a more generalized condition of alienation. In the 1970s critics hypothesized that this alienation could be ascribed to the emergence of audio/visual recording and the proliferation of the mediated experiences these technologies made possible. In response to such concerns, the artists I consider produced works that posed a challenging question: can mediated, virtual forms of experience possess positive values that accord with traditional humanist ideals, or are they characterized exclusively by alienation and absence? Using lip-sync to figure these concerns, these video artists come to different conclusions. Their lip-sync failures function variously to document, to criticize and to celebrate the postmodern debasement of auditory presence at the level of the subject’s body.